Internet of things based autonomous robot system architecture for home automation and healthcare services - Karuna Sagar, Bhimunipadu Jestadi Job; Latha, Garapati Swarna; Bolla, Sreenivasulu; Nanajkar, Jyotsna Amit; Patnala, Pattabhirama Mohan; Mande, Praveen; Kharde, Mukund Ramdas; Narasimharao, Jonnadula (Indonesian Journal of Electrical Engineering and Computer Science, 2025)
The internet of things (IoT) is playing a major role in the development of the health industry by enabling more accessible and affordable virtual and distant patient contacts through applications that are easy to use. The IoT and automated homes are becoming more popular in recent days. A network of connected devices, including hardware, equipment, and technical support, is known as the IoT. Their purpose is to allow data exchange with other systems through the internet. This paper presents, internet of things based autonomous robot system architecture (IoT-ARSA) for home automation and healthcare services. The primary goal of this secure home automation system is to help the elderly and disabled people by allowing them to operate home appliances. Additionally, the system uses a cloud server to predict the health conditions of patients and the elderly people, providing information to a guardian. The patient's health condition is determined using sensors like temperature, pulse, blood pressure, and oxygen level. Ultrasonic sensor and face detection are used for home automation. Each sensor will interact with the Raspberry Pi 4 to record data, which will then be processed and stored in the cloud. From results it is clear that described (IoT-ARSA) for home automation and healthcare services model is very efficient with high accuracy and high security. Health monitoring is achieved with this model continuously with great efficiency.